1981
DOI: 10.1002/aic.690270106
|View full text |Cite
|
Sign up to set email alerts
|

A branched pore kinetic model for activated carbon adsorption

Abstract: A branched pore kinetic model for aqueous phase activated carbon adsorption is presented in which the carbon particle is separated into rapidly and slowly diffusing regions. The model was developed to overcome problems arising from a single rate parameter analysis and is shown to describe experimental data well. In addition to very different rates of transport in the two regions, parameters estimated by regression analysis indicated differences in the adsorptive characteristics. RUSSELL G. PEEL SCOPEActivated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
10

Year Published

1985
1985
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(59 citation statements)
references
References 20 publications
(19 reference statements)
2
46
1
10
Order By: Relevance
“…Homogeneous solid surface diffusion models have been developed for the adsorption of phenol onto activated carbon using the Crank-Nickolson ® nite difference method to solve the diffusion equation 53 , the adsorption of phenolic compounds onto carbon using orthogonal collocation to solve the diffusion equation 54 and the adsorption of basic dyes onto silica 55 and basic dyes onto activated carbon 56 , using a semi-analytical solution to solve the diffusion equation. Branched pore diffusion models based on macro-, meso-and micropore diffusion have been developed for phenol adsorption 57 and dye adsorption on activated carbon 58 . The application of variable surface diffusivity to the HSDM has been studied in several cases 59 61 .…”
Section: Analysis Of Data From the Literaturementioning
confidence: 99%
“…Homogeneous solid surface diffusion models have been developed for the adsorption of phenol onto activated carbon using the Crank-Nickolson ® nite difference method to solve the diffusion equation 53 , the adsorption of phenolic compounds onto carbon using orthogonal collocation to solve the diffusion equation 54 and the adsorption of basic dyes onto silica 55 and basic dyes onto activated carbon 56 , using a semi-analytical solution to solve the diffusion equation. Branched pore diffusion models based on macro-, meso-and micropore diffusion have been developed for phenol adsorption 57 and dye adsorption on activated carbon 58 . The application of variable surface diffusivity to the HSDM has been studied in several cases 59 61 .…”
Section: Analysis Of Data From the Literaturementioning
confidence: 99%
“…Transfer rate of solute from macropore to micropore: (Peel et al, 1981;Yang and Al-Duri, 2001;Ko et al, 2002) Shrinking core theory model This model used to describe the intrapellet adsorption is controlled by pore diffusion, supposing adsorption firstly occurs at the outer region of adsorbent, then the mass transfer zone moves inward together with the extending of saturated outer region and shrinking of unloaded core (Fig. 5) The mass transfer flux at the solid-liquid phase interface: Du et al, 2007;2008) To be continued A review of surface diffusion is available elsewhere (Medved and Cerny, 2011), which might provide some ideas to modify the intrapellet diffusion models.…”
Section: General Rate Modelsmentioning
confidence: 99%
“…Study of pore size heterogeneity revealed the variation of adsorbate diffusivity within the porous adsorbent [23,39,40]. These processes have been modelled as a fractal-like dependence of diffusion coefficient [34,41,42], or to involve correlated variables, by categorising the adsorption kinetics into macropore and micropore diffusional regions, respectively [32,39,43]. As a key element for assessing the adsorption performance, the importance of surface diffusion in contributing to the total adsorbent mass transfer in porous materials has been highlighted in many liquid-surface adsorption systems [44,45].…”
Section: Introductionmentioning
confidence: 99%